Diagnosis and Surgico-Therapeutic Management of Bovine Tumours - Panchal, Jay H; Bhatt, Raghuvir H; Raval, Rupesh J; Kalaria, Vinay A; Vadalia, Jignesh V (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was conducted on total 93 bovine tumour cases registered at Veterinary Clinical Complex of the College at Junagadh  (India) to diagnose and surgically manage them. Each case was evaluated by taking detailed history and clinical examination followed  by different diagnostic procedures like ultrasonography and thermography as per the need. Out of 93 cases of bovine neoplasm, 52  cases were confirmed of horn cancer; 20 cutaneous tumours included 5 tumours of head region, 4 cases of udder tumours, 4 cases of  neck tumour, 4 cases of tumours at different parts of limb and 3 tumours at abdominal region; 8 cases were of genital tumour; 7 cases of  eye cancer; 4 cases of odontoma, and 2 cases of nasal granuloma. After diagnosis, all the cases were managed by surgical excision alone  or in combination with cryotherapy and chemotherapy. Histopathological examination of excised tumour mass was carried out which  revealed 48 (51.61%) benign tumours, whereas 45 (48.39%) cases were malignant in nature. Among a total of 93 cases, there were 45  (48.39%) cases of squamous cell carcinoma, 15 (16.13%) cases of myxoma, 14 (15.05%) cases of fibroma, 10 (10.75%) cases of melanoma,  8 (8.60%) cases of papilloma and one (1.08%) case of haemangioma, which were treated accordingly. After surgico-chemotherapeutic  management, animals recovered uneventfully. Moreover, improvement in their life was noticed after appropriate management.
Keywords: Bovine tumours; Diagnosis; Histopathology; Surgical management; Thermography; Ultrasonography